2009
DOI: 10.1146/annurev.pathol.4.110807.092239
|View full text |Cite
|
Sign up to set email alerts
|

NOD-Like Receptors: Role in Innate Immunity and Inflammatory Disease

Abstract: The NOD-like receptors (NLRs) are a specialized group of intracellular receptors that represent a key component of the host innate immune system. Since the discovery of the first NLR almost 10 years ago, the study of this special class of microbial sensors has burgeoned; consequently, a better understanding of the mechanism by which these receptors recognize microbes and other danger signals and of how they activate inflammatory signaling pathways has emerged. Moreover, in addition to their primary role in hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
534
0
15

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 647 publications
(560 citation statements)
references
References 172 publications
5
534
0
15
Order By: Relevance
“…TLR2 receptors, while acting as sensors for extracellular cues or the endocytic network, drive signaling events in response to recognition of pathogen-associated molecular patterns, including mycobacterial antigens like ESAT-6, PE_PGRS antigens; NOD1 and NOD2 operate as cytosolic sensors initiating signaling pathways upon recognition of diaminopimelic acid and muramyl dipeptide (MDP), components of bacterial peptidoglycan (15)(16)(17)(18)(19)(20). Although TLR2 or NOD receptor-induced signaling events culminate in activation and nuclear translocation of NF-B, transcriptome profiles in response to TLR2 or NOD receptors could markedly diverge.…”
mentioning
confidence: 99%
“…TLR2 receptors, while acting as sensors for extracellular cues or the endocytic network, drive signaling events in response to recognition of pathogen-associated molecular patterns, including mycobacterial antigens like ESAT-6, PE_PGRS antigens; NOD1 and NOD2 operate as cytosolic sensors initiating signaling pathways upon recognition of diaminopimelic acid and muramyl dipeptide (MDP), components of bacterial peptidoglycan (15)(16)(17)(18)(19)(20). Although TLR2 or NOD receptor-induced signaling events culminate in activation and nuclear translocation of NF-B, transcriptome profiles in response to TLR2 or NOD receptors could markedly diverge.…”
mentioning
confidence: 99%
“…This signaling induces proinflammatory cytokines, chemokines, adhesion molecules, and inflammasome components, all of which facilitate effector responses (1,2). A second family of receptors, nucleotide-binding oligomerization domain-like like receptors (NLRs), reside in the cytosol and are activated in response to either microbial ligands that gain access to the cytosol or virulence factors, such as bacterial toxins (3,4).…”
Section: Immunologymentioning
confidence: 99%
“…Mutations in NOD1 and NOD2 leading to loss or gain of function are associated with autoimmune and inflammatory diseases (19,(45)(46)(47)(48)(49). We previously reported that the NOD2 mutation associated with severe Crohn's disease (3020C) results in enhanced HCMV replication in vitro (13).…”
Section: Discussionmentioning
confidence: 99%